2002
DOI: 10.1246/bcsj.75.1977
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mono-Dispersed Mesoporous Silica Spheres with Hexagonal Symmetry

Abstract: Mono-dispersed mesoporous silica spheres with ordered hexagonal regularity were synthesized from tetramethoxysilane and dodecyltrimethylammonium bromide as a surfactant under very specific conditions. By adjusting the optimum concentrations of the reactants, silica particles with diverse morphology were obtained at higher initial concentrations. Dilution of the reactants led to the formation of silica spheres with various sizes and relatively less mesoporous regularity. Mono-dispersed silica spheres could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…On the other hand, primary particles aggregated at low surfactant/Si ratios because of the hydrophobic interactions between the surfactants that were not involved in the mesostructure formation but were adsorbed onto the nanoparticles without the formation of micelles. In addition, the use of a large amount of organic solvents that increase the critical micelle concentration may also cause the aggregation of mesostructured silica nanoparticles, as considered from the preparative conditions reported by Yano et al 21,42,79 Therefore, it should be important to use a high surfactant/Si ratio in the preparation of colloidal mesostructured silica nanoparticles.…”
Section: Major Factors For Preparation Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, primary particles aggregated at low surfactant/Si ratios because of the hydrophobic interactions between the surfactants that were not involved in the mesostructure formation but were adsorbed onto the nanoparticles without the formation of micelles. In addition, the use of a large amount of organic solvents that increase the critical micelle concentration may also cause the aggregation of mesostructured silica nanoparticles, as considered from the preparative conditions reported by Yano et al 21,42,79 Therefore, it should be important to use a high surfactant/Si ratio in the preparation of colloidal mesostructured silica nanoparticles.…”
Section: Major Factors For Preparation Ofmentioning
confidence: 99%
“…Yano et al succeeded in preparing pore-expanded MSNs through a post-treatment method ( Figure 34). 347349 Surfactants of mesostructured silica nanoparticles were exchanged with 21 In addition, Mou et al have prepared colloidal MSNs with a highly ordered structure. 29 Suteewong et al have reported preparing MSNs possessing a cubic structure by using very high molar ratios of 3-aminopropyltriethoxysilane.…”
Section: Soft Template;mentioning
confidence: 99%
See 1 more Smart Citation
“…100 nm in diameter are expected to be useful for applications in DDS and transparent media such as low-refractive index materials, thermal insulation films, and low dielectric materials [6][7][8][9][10][11][12][13][14]. However, it has been difficult to synthesize monodisperse porous silica particles of 100 nm in diameter on an industrial scale, because the synthesis should take place in highly diluted solutions [10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. We recently reported the large-scale synthesis of monodisperse microporous silica particles of 100 nm in diameter [31], based on the modified Stöber method [32].…”
Section: Introductionmentioning
confidence: 99%
“…In later studies, hydrolysis was run in the presence of different surfactants in order to control the granule size [40]. The effect of surfactants on the size and properties of SiO 2 granules was studied in detail by Yono et al [41]. Varying the surfactant (cetyltrimethylammonium chloride) : NH 4 OH ratio, one can tune not only the size of the resulting SiO 2 granules but also their porosity, reducing the pore size down to 2-3 nm [42].…”
Section: Introductionmentioning
confidence: 99%